The way wear goes: phytolith-based wear on the dentine–enamel system in guinea pigs (Cavia porcellus). Issue 1912 (9th October 2019) - Martin, Louise F.; Winkler, Daniela; Tütken, Thomas; Codron, Daryl; De Cuyper, Annelies; Hatt, Jean-Michel; Clauss, Marcus
Abstract : The effect of phytoliths on tooth wear and function has been contested in studies of animal–plant interactions. For herbivores whose occlusal chewing surface consists of enamel ridges and dentine tissue, the phytoliths might particularly erode the softer dentine, exposing the enamel ridges to different occlusal forces and thus contributing to enamel wear. To test this hypothesis, we fed guinea pigs ( Cavia porcellus ; n = 36 in six groups) for three weeks exclusively on dry or fresh forage of low (lucerne), moderate (fresh timothy grass) or very high (bamboo leaves) silica content representing corresponding levels of phytoliths. We quantified the effect of these treatments with measurements from micro-computed tomography scans. Tooth height indicated extreme wear due to the bamboo diet that apparently brought maxillary incisors and molars close to the minimum required for functionality. There were negative relationships between a cheek tooth's height and the depth of its dentine basin, corroborating the hypothesis that dentine erosion plays an important role in herbivore tooth wear. In spite of lower body mass, bamboo-fed animals paradoxically had longer cheek tooth rows and larger occlusal surfaces. Because ever-growing teeth can only change in shape from the base upwards, this is a strong indication that failure to compensate for wear by dental height-growth additionally triggered general expansive growth of the tooth bases. The results suggest that enamel wear may intensify after enamel has been exposed due to a faster wear of the surrounding dentine tissue (and not the other way around), and illustrate a surprising plasticity in the reactivity of this rodent's system that adjusts tooth growth to wear.